GENDER AND REGIONAL CHARACTERISTICS OF PHARMACOEPIDEMIOLOGY OF POST-COVID-19 ASSOCIATED DIGESTIVE DISEASES - Mamasaliev N.S; Boltaboev A.M; Tursunov X.X; Mamasaliev Z. N; Usmonov B.U; Boltaboeva D.I (Scholar Express Journals, 2025)
The fact that the flow of studies and publications devoted to the Covid-19 pandemic has increased and continues to increase worldwide is evident from the literature review or the reader-researcher may conclude that this is an indication that there are still “mysteries” in the Covid-19 infection. Among these problems, the issue of studying the epidemiology, prevention and radical improvement of treatment methods for Post-Covid-19-associated digestive system diseases is also a cross-cutting and acute medical and social problem.
Keywords: COVID-19; Post-Covid-19; associated digestive system diseases